Ocular Injuries: Its Etiology and Consequences in Balochistan - Khalid Hameed, Barkat Jamali, Muhammad Akram Shahwani (Pakistan Journal of Ophthalmology, 2006)
Purpose: To find out the etiologies and consequence of ocular injuries presented in Helper eye hospital Quetta, Blochistan. We analysed 200 cases of Ocular injuries in Helpers Eye Hospital, Quetta regarding its etiology in three different age groups of 0-15, 16-30 and above 30 years of ages. Material and Methods: Retrospective analysis of 200 cases of ocular injuries was done who presented in the eye department of the Helper eye hospital Quetta Blochistan. Data was recorded on the proforma for further analysis. Recording were made specifically for age, sex and type of injury patients were divided into three groups according to age 0-15, 15-30 and above 30 years to find out the comment injury in each age group. Results: The majority 48.5 % (n=97) was due to sports and play, maximum being in children (n=87). Occupational and firearm injuries were the second commonest cause (12.5 %) n=25 and 12 % (n=24) respectively. Whereas fight and assault was found responsible in 10 % (n=20) and road traffic accident 6.5 % (n=13) in our study. Conclusion: Keeping in view the above etiological factors it is being emphasized that efforts should be made towards the prevention, and proper management of Ocular injuries in Pakistan. Key words: Ocular trauma, Blochistan.